Exploiting interspecific conservation of male-specific genomic regions to develop markers for sex determination in catla (Labeo catla) and silver carp (Hypophthalmichthys molitrix) - Hamilton, Matthew G.; Akhter, Md. Masud; Shanta, Sirajum Monira; Roy, Aashish Kumar; Rahman, Md. Mustafizur; Sarkar, Uzzal Kumar; Kamruzzaman, Md.; Benzie, John A.H. (Elsevier, 2026)
This study aimed to identify and validate male-specific genomic markers for two economically significant aquaculture species: catla (Labeo catla syn. Catla catla) and silver carp (Hypophthalmichthys molitrix). Using conserved male-specific genomic regions from closely related species—rohu (Labeo rohita) and bighead carp (Hypophthalmichthys nobilis)—short sequence fragments were aligned to catla and silver carp genome assemblies to identify candidate male-specific markers. These markers were incorporated into DArTag panels and evaluated, according to read-count thresholds, in individuals of known visually-assessed or functional (i.e. reproductive) phenotypic sex (PSEX). Consistent with a XX/XY sex determination system, the sequences were expected to be present in males and absent in females. In catla, three markers predicted functional PSEX with 94.7 % accuracy. Notably 10 out of 123 genotyped catla dams were marker-assigned a genotypic sex (GSEX) of male, likely due to the presence of marker sequences in non-sex-determining genomic regions. For silver carp, 11 markers demonstrated a very high accuracy of 99.7 % in predicting visually-assigned PSEX. The markers and methods identified in this study represent promising tools for efficient and accurate sex determination in catla and silver carp, though further validation across different populations is recommended to ensure their broader applicability. The identified markers showed strong potential for practical application in aquaculture, particularly for the quantification of sexual dimorphism in immature fish and identification of sex-reversed individuals, in addition to their use in genetic improvement programs.